Phenylethynyl-substituted heterocycles inhibit cyclin D1 and induce the expression of cyclin-dependent kinase inhibitor p21Wif1/Cip1 in colorectal cancer cells. Issue 1 (22nd November 2017) - Sviripa, Vitaliy M.; Kril, Liliia M.; Zhang, Wen; Xie, Yanqi; Wyrebek, Przemyslaw; Ponomareva, Larissa; Liu, Xifu; Yuan, Yaxia; Zhan, Chang-Guo; Watt, David S.; Liu, Chunming
Abstract : Fluorinated phenylethynyl-substituted heterocycles inhibit cyclin D1, induce cyclin-dependent kinase inhibitor-1 and block the proliferation of colorectal cancer cells. Abstract : Fluorinated phenylethynyl-substituted heterocycles that possessed either an N -methylamino or N, N -dimethylamino group attached to heterocycles including pyridines, indoles, 1 H -indazoles, quinolines, and isoquinolines inhibited the proliferation of LS174T colon cancer cells in which the inhibition of cyclin D1 and induction of the cyclin-dependent kinase inhibitor-1 ( i.e., p21 Wif1/Cip1 ) served as readouts for antineoplastic activity at a cellular level. At a molecular level, these agents, particularly 4-((2, 6-difluorophenyl)ethynyl)- N -methylisoquinolin-1-amine and 4-((2, 6-difluorophenyl)ethynyl)- N, N -dimethylisoquinolin-1-amine, bound and inhibited the catalytic subunit of methionine S -adenosyltransferase-2 (MAT2A).